Pengaruh Rekrutmen Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Brataco Medan - Suhaila Suhaila; Wan Suryani; Teddi Pribadi (Universitas Medan Area, 2021)
The purpose of this study was to determine and analyze the Effect of Job Recruitment and Discipline on Employee Performance of PT.Brataco Medan Branch The research method used is associative research, where variables are measured on a Likert scale. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were employees at PT.Brataco Medan Branch, totaling 62 people. Sampling with saturated sampling method or better known as the census. In this study the total population is relatively small as many as 62 people. Data processing using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis. The results showed that: (1) partially Recruitment variables affected the performance of the employees of PT.Brataco Medan Branch, (2) partially the Work Discipline variables affected the performance of the employees of PT.Brataco Medan Branch (3) simultaneously there were positive and significant influences between variables Job Recruitment and Discipline affects the performance of PT.Brataco Medan Branch Employees